The elephant in the bathtub: when the physics of star formation regulate the baryon cycle of galaxies - Gensior, Jindra; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2021)
In simple models of galaxy formation and evolution, star formation is solely regulated by the amount of gas present in the galaxy. However, it has recently been shown that star formation can be suppressed by galactic dynamics in galaxies that contain a dominant spheroidal component and a low gas fraction. This ‘dynamical suppression’ is hypothesized to also contribute to quenching gas-rich galaxies at high redshift, but its impact on the galaxy population at large remains unclear. In this paper, we assess the importance of dynamical suppression in the context of gas regulator models of galaxy evolution through hydrodynamic simulations of isolated galaxies, with gas-to-stellar mass ratios of 0.01-0.20 and a range of galactic gravitational potentials from disc-dominated to spheroidal. Star formation is modelled using a dynamics-dependent efficiency per free-fall time, which depends on the virial parameter of the gas. We find that dynamical suppression becomes more effective at lower gas fractions and quantify its impact on the star formation rate as a function of gas fraction and stellar spheroid mass surface density. We combine the results of our simulations with observed scaling relations that describe the change of galaxy properties across cosmic time, and determine the galaxy mass and redshift range where dynamical suppression may affect the baryon cycle. We predict that the physics of star formation can limit and regulate the baryon cycle at low redshifts (z ≲ 1.4) and high galaxy masses (M* ≳ 3 × 1010 M⊙), where dynamical suppression can drive galaxies off the star formation main sequence.